1996
DOI: 10.1177/154596839601000107
|View full text |Cite
|
Sign up to set email alerts
|

Disability Changes After Treatment of Upper Limb Spasticity with Botulinum Toxin

Abstract: We performed an open label single-blind trial with seventeen patients with moderate to severe upper limb spasticity following stroke or traumatic brain injury, treated with an average dose of 165 MU (mouse units) botulinum toxin (range: 100 MU to 210 MU). Evaluation of outcome was carried out analyzing the changes in standard measures of impairment, disability, and quality of life. Spasticity reduction, with increased range of motion (ROM), was observed in all patients, independent of the duration of spasticit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 12 publications
(8 reference statements)
0
15
0
Order By: Relevance
“…This finding substantiated a recent similar report (9) . Above results also showed significant improvement in Motricity index as compared to more generalised Functional Independence Measure (10,11) . Focal improvement of function were significantly detected by Motricity Index .Which tested key functional aspect of a particular joint muscle group.…”
Section: Modified Ashworth Scalementioning
confidence: 57%
“…This finding substantiated a recent similar report (9) . Above results also showed significant improvement in Motricity index as compared to more generalised Functional Independence Measure (10,11) . Focal improvement of function were significantly detected by Motricity Index .Which tested key functional aspect of a particular joint muscle group.…”
Section: Modified Ashworth Scalementioning
confidence: 57%
“…The ef cacy of BTX-A treatment on tone and PROM was demonstrated by the RCT performed by Simpson et al (57) and supported by other studies (58,59,(61)(62)(63)(64)(65)(66). In addition, Hesse et al (60) found evidence of a synergistic effect of ES combined with BTX-A treatment.…”
Section: Botulinum Toxinmentioning
confidence: 68%
“…After the preliminary assessment, 12 studies were included for detailed methodological evaluation (57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68). Ten studies focused on the treatment of upper limb spasticity with BTX-A (57-66), one focused on alcohol neurolysis (67) and one study dealt with phenol neuromuscular blockade (68).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32][33] [35][36][37][38][39][40][41][42][43][44] As an extension to a 12-week double-blind study, 41 111 patients were enrolled in a 42-week open label study. 45 In this study, repeated BTX injections for upper limb spasticity have resulted in significant and sustained improvement in both Disability Assessment and Ashworth Scores.…”
Section: Btx For Upper Limb Spasticitymentioning
confidence: 99%